Pengembangan Modul E-Learning pada Mata Pelajaran Simulasi dan Komunikasi Digital SMK N 1 Padang - Yunike Wulandari; Fahmi Rizal; Edidas Edidas (Pedagogi: Jurnal Ilmu Pendidikan, 2020)
This study aims to develop e-learning based modules to increase student motivation in Simulation and Digital Communication subjects at SMK N 1 Padang. The research method used is research and development using the Borg and Gall model which is limited to five research steps namely the data collection stage, the planning stage, the product development stage, the initial field trial stage, and dissemination. The object of the trial in this study was students of class X Machining C Engineering at SMK N 1 Padang, amounting to 33 people. The research instruments used were material expert validation sheets, media expert validation sheets, professional teacher response questionnaire, student response questionnaire, multiple-choice question instrument, and student motivation questionnaire. The results of the material expert validation showed 82.81% (very good). The results of the validation of the media experts showed 79.13% (very good). The results of professional teacher simulation and digital communication responses covered all aspects of the material and media at 86.71% (very good) and the results of student responses were obtained 80.20% (very good). The results of the student learning motivation questionnaire showed 85.13% (very good). To find out the increase in the achievement of knowledge competence is done by giving pre-test, treatment, post-test (Pretest-Posttest Control Group Design) through the T-test, the results of the assessment on digital citizenship material obtained N-Gain 0.85 high category. Based on the data above, this study shows that the development of e-learning modules in Simulation and Digital Communication subjects can increase student motivation.